NATURE IS OF ANOMALY ELECTRICAL CONDUCTIVITY SOME COLLECTORS OF DNIPROVSKO-DONETSKA DEPRESSION - SHEPEL, S.; RYBAK, L.; KONDRATIEVA, N.; RIABUKHA, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
On fundamentals laboratory specifics of electrical prospecting some dry and airdry sedimentary rocks DD depression was demerminated phisics nature of their anomaly high electrical conductivity. Character sandstones, siltstones, argillites was researched in different frequency range of electromagnetic field.